Preparation and application of pine-magnetite composite grafted with functional vinyl monomers for removal of dyes from single and binary solutions - Mtshatsheni, Kgomotso Ntombizodwa Gina (Vaal University of Technology, 2021)
Water is a basic resource to mankind. The environment is deteriorating daily due to industrial pollution of water resources. Industrial effluents containing organic pollutants such as dyes are undesirable even at low concentrations in the environment. Natural biomaterials have been applied as adsorbents for dye removal from water systems, however, their application has been limited by their low adsorption capacity. Much attention has been focused on the chemical modification of natural biomass via grafting processes. The modification of natural polymers by graft copolymerization is a promising technique since it functionalizes a biopolymer thus imparting desirable properties. The purpose of the study was to prepare and optimize the working conditions for the pine-magnetite bionanocomposites (PMC) as adsorbents and as photocatalysts modifiers. First, this work focuses on the synthesis and optimization of reaction variables in the preparation of PMC for the removal of methylene blue (MB). The thesis also explores the synthesis of acrylamide and acrylic acid-grafted PMC, resulting in the formation of acrylamide-grafted PMC (GACA) and acrylic acid-grafted pine-magnetite bionanocomposites (GAA), respectively. The grafting of functional groups such as –CO, –NH2 onto cellulose from acrylamides is also explored in detail. The adsorption conditions optimized were used to investigate the adsorption efficiency of GAA and GACA on MB. Finally, the application of PMC and GAA as modifiers for amorphous TiO2 and N-doped TiO2was carried out. The photocatalytic bionanocomposites from PMC (namely PMC–a-C,TiO2 and PMC–a-C,NTiO2) and those from GAA (labeled GAA–a-C,TiO2 and GAA–a-C,NTiO2) are compared by their photocatalytic efficiency on the degradative removal of an alkaline dye mixture formed from Reactive red 120 (RR 120) and Rhodamine B (Rh B). The synthesis procedure for PMC involved treating pinecone biomass with 0.15 M NaOH solution to remove unwanted plant extracts and the subsequent coating of the treated pinecone with iron oxide magnetic particles through a co-precipitation method. The variables used for the experiments were volume of NH4OH (5 to 40 cm3), reaction temperature (40 to 100 °C), effect of time (15 to 60 min) and mass (1.0 to 3.5 g). The PMC and acrylic acid grafted pine-magnetite composite (GAA) were probed for structural morphology and surface properties using various surface characterization instrumental techniques. Strong chemical interactions between pinecone magnetite and acrylic acid were demonstrated by thermogravimetric (TGA), differential thermal analysis (DTA) and X-ray photoelectron spectroscopy (XPS) for these unique bionanocomposites as such suggesting high chemical stability. Grafting acrylic acid was shown by XPS to form polyacrylic acid on the surface of the bionanocomposites and thus capping the surface groups. Significant differences in size were shown by transmission electron spectroscopy (TEM) and scanning electron microscopy (SEM); i.e., smaller particle sizes (Ave = 13.0 nm) for GAA and slightly larger for PMC (Ave = 14.0 nm). Brunauer Emmett Teller (BET) surface analysis demonstrated a larger surface area, pore volume and pore diameter (59.9 m2.g-1, 0.2254 cm3.g-1 and 28.14) for GAA compared to PMC. These characteristics coupled with the point of zero charge for GAA (pHpzc = 6.8) were critical in enhancing the efficiency of GAA adsorption of MB at pH 12 and further enable GAA to have a higher desorption efficiency of up to 99.7% after four cycles of washing with 0.10 M HCl. The adsorption kinetics and isotherm studies indicated that the adsorption process follows the pseudo second order kinetics and Langmuir isotherm respectively. The adsorbent also showed improvement in the adsorption capacity and reusability promising to be used for the removal of dyes in a prototype scale. GAA and MB adsorption mechanism was confirmed to be through intra particle diffusion. The overall performance of the GAA bionanocomposites is hinged on the formation of polyacrylic acid on the surface, its structural morphology, and the enhanced surface properties. Most importantly, the plant-based materials (lignin and cellulose) provide an environment that is rich with surface (–COOH and –OH) groups for the attachment of the magnetite nanoparticles while the polyacrylic acid stabilizes the magnetite onto the pinecone nanoparticles while reducing the point of zero charge for increased adsorption of cationic species. The photocatalytic bionanocomposites were fabricated from the adsorptive bionanocomposites using a simple solgel process in which ~10 wt.% of PMC and GAA, respectively, were used as a starting agent. Titanium butoxide was used as a precursor, acetylacetone as a dispersant and ethylene diamine as a nitrogen source. Using this procedure, amorphous carbon-doped titania (a-C,TiO2) and amorphous carbon and nitrogen co-doped titania (a-C,NTiO2) were fabricated except that the biopolymer was not added. Two sets of amorphous titania bionanocomposites were fabricated. One set was the nitrogen doped forms that had been modified with PMC and GAA (PMC–a-C,TiO2 and GAA–a-C,NTiO2). The other set of photocatalytic bionanocomposites produced in this work were without nitrogen (PMC–a-C,TiO2 and GAA–a-C,TiO2). TEM and SEM micrographs showed that all the photocatalysts consisted of globular, smooth aggregates of nanosized a-CTiO2 and a-C,NTiO2 which decreased in size with N-doping and the incorporation of GAA and PMC to as low as <30 nm. Surface chemical analysis through FTIR, XPS and EDS confirmed the presence of C, O, Ti and N (for the N-doped photocatalysts). In addition, it was demonstrated that N-doping into TiO2 had taken place, albeit with most of the N incorporated as organic nitrogen. It was further demonstrated that because of the absence of high temperature calcination, the process chemicals played a significant role in doping the photocatalysts with carbon resulting in the promotion of photocatalytic activity for a-C,TiO2 to the point of surpassing that of, a-C,NTiO2 and all the PMC-modified photocatalytic bionanocomposites. a-C,TiO2 had an overall 94% removal of the dyes, Rhodamine B (RhB) and Reactive red 120(RR 120), under UV illumination. The benefit of co-doping a-TiO2 with C, N and the biopolymers was realized with the incorporation of GAA as a modifier. The result was 97% removal of the dyes by GAA–a-CTiO2 and 99% for GAA–a-C,NTiO2. It was further observed that the degradation of the binary mixture of the dyes (RhB and RR 120) proceeded through the zero order kinetics for the a-C,TiO2 based photocatalysts and first order kinetics for the N-doped photocatalysts. The work, has, therefore demonstrated the applicability of plant-based biopolymers in the fabrication of nanoadsorbents and nanophotocatalysts. While the photocatalytic degradations were carried out under UV-light, there still remains a number of possible avenues that researchers can build on to improve the visible light-driven photocatalytic bionanocomposites. The research work has proven the effectiveness of novel pinecone magnetic nanoparticle materials and TiO2-based photocatalyst for the degradation of undesirable dyes from wastewater.
Ph. D. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Pinecone biomass; Pine-magnetite composite; Nanoadsorbents; Nanophotocatalysts; Photocatalytic bionanocomposites; Methylene blue dye; Dissertations, Academic -- South Africa.; Water -- Pollution.; Dyes and dyeing -- Textile fibers, Synthetic.; Water -- Purification -- Photocatalysis.